The scattering of surface plasmon polaritons by nanoscale surface defects - Maradudin, A.A.; Leskova, T.A.; García-Guerrero, E.E.; Méndez, E.R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
A rigorous computational approach based on Green’s second integral identity in the plane is used to calculate the transmission, reflection, and conversion into volume electromagnetic waves of a surface plasmon polariton incident on a nanoscale one-dimensional surface defect on an otherwise planar interface between vacuum and a lossy metal.